2009
DOI: 10.1111/j.1420-9101.2009.01770.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coil phenotypes and genotypes on the fecundity and viability of Partula suturalis and Lymnaea stagnalis: implications for the evolution of sinistral snails

Abstract: Why are sinistral snails so rare? Two main hypotheses are that selection acts against the establishment of new coiling morphs, because dextral and sinistral snails have trouble mating, or else a developmental constraint prevents the establishment of sinistrals. We therefore used an isolate of the snail Lymnaea stagnalis, in which sinistrals are rare, and populations of Partula suturalis, in which sinistrals are common, as well as a mathematical model, to understand the circumstances by which new morphs evolve.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…This ratio differed from the 1∶1 expected ( Χ 2  = 7.221; P <0.007). As it has previously been shown [13], [14] that a high proportion of embryos fail to develop from a mother that is genetically sinistral, dd , then we speculate that one explanation is differential mortality of dd individuals compared with Dd individuals from a common dd mother.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…This ratio differed from the 1∶1 expected ( Χ 2  = 7.221; P <0.007). As it has previously been shown [13], [14] that a high proportion of embryos fail to develop from a mother that is genetically sinistral, dd , then we speculate that one explanation is differential mortality of dd individuals compared with Dd individuals from a common dd mother.…”
Section: Resultsmentioning
confidence: 57%
“…It is presumed that it is this factor, or an intermediate, that then goes on to direct the dynamics of later chiral blastomere division [11]. It has also been shown that the early development in sinistrals is not an exact mirror image of development in dextrals [12], with many sinistral embryos failing to develop at all [13], [14]. In the last few years, the work on Lymnaea has been given added impetus because it has been discovered that a common gene, nodal , links deuterostome and molluscan asymmetry, although in neither case is it the earliest symmetry breaking determinant [11], [15].…”
Section: Introductionmentioning
confidence: 99%
“…In dextral species, the right lobe is bigger (e.g., Koene et al, 2000) and in sinistral species it is the left one (e.g., B. glabrata : Lever et al, 1965; L. stagnalis : Davison et al, 2009), in concordance with the side where the male organs are located. The different neuropeptides that have been reported to be present in the right anterior lobe are summarized in Figure 1 and Table 1.…”
Section: Male Reproductive Behavior and Its Neuro-endocrine Controlmentioning
confidence: 95%
“…Another hypothesis suggests that developmental constraint prevents the establishment of sinistral forms. Davison et al (2009) studied the effect of coil phenotypes and genotypes on the fecundity and viability of fully self-fertilized hermaphrodite species (Lymnaea stagnalis), in addition to hermaphrodite species, which are rarely self-fertilized (Partula suturalis). These authors concluded that the sinistral genotype is associated with reduced egg viability in Lymnaea stagnalis; however, that individuals of the sinistral and dextral genotypes appear equally fecund in Partula suturalis.…”
mentioning
confidence: 99%